Examining the Relationship between Salivary Amylase Level, Head Trauma Severity and CT Scan Results in Patients with Isolated Mild Head Trauma - Mohsen Ebrahimi; Behrang Rezvani Kakhki; Baharak Davoudpour; Zahra Abbasi Shaye; Hossein Zakeri; Seyed Mohammad Mousavi; Sayyed Majid Sadrzadeh; Seyed Aliakbar Shamsian; Azadeh Mahmoudi Gharaee (Bulletin of Emergency and Trauma, 2022)
Objective: To investigate the relationship between salivary amylase level and computed tomoraphy (CT scan) findings in patients with isolated mild traumatic Brain Injury (mTBI) referred to the emergency department of Shahid Hasheminejad Hospital. Methods: Patients with isolated mTBI and indication for brain CT scan who referred to the trauma center of Shahid Hasheminejad Hospital, Mashhad, Iran in 2019 were included in a cross-sectional study. In the initial examination, the patient’s level of consciousness was measured using the Glasgow Coma Scale (GCS), and saliva samples were taken at the emergency department to determine the level of salivary amylase. A brain CT scan was performed for all patients. Age, gender, cause of trauma, the trauma severity and CT scan results were recorded. Statistical analysis was performed on the data. Results: One-hundred fifty patients were enrolled in this study (men=101, women=49). The trauma causes were included accidents (n=88; 58%), falls (n=37; 25%) and miscellaneous factors (e.g., quarrels; n=25; 17%). GCS was 15 in 142 patients and 14 in the rest. In all patients, the trauma severity was mild to high risk (Minor). CT scan results unfolded pathology in 10 cases (7%), while the residues (93%) had normal CT scans with no pathological evidence. Salivary amylase level in the patients’ saliva samples was between 137 to 8000 units per liter. Using the t-test to evaluate the relationship between salivary amylase levels and CT scan results uncovered a significant relationship. Spearman correlation revealed no significant relationship between the amylase and GCS levels. Conclusion: Data statistical analysis from 150 patients with isolated head trauma manifested that salivary amylase levels were significantly higher in the patients with pathological findings on CT scans. However, no significant relationship was found between salivary amylase level and age, gender, cause of trauma, and level of consciousness.